Analysis of series/parallel multilevel inverter with symmetrical and asymmetrical configurations - Motaparthi Nagaraju; Malligunta Kiran Kumar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
Usage of high power and medium voltage applications in domestic and industrial purpose has been increased in the recent years. Also, the penetration of renewable energy sources is increasing rapidly. To make use the renewable energy sources there is a need of using inverters. The basic inverter is conventional two level inverter which produces the square wave output voltage. The major drawback of conventional inverter is it contains more harmonics. Therefore, multilevel inverters have been introduced with staircase output voltage waveform. Lot of multilevel inverter topologies have been developed and cascaded H bridge type is the more frequently used. But, it requires more number of switches for higher output voltage level. In this paper, a novel 7 level asymmetrical multilevel inverter topology is proposed with less number of switches. This proposed topology is compared with already existing topology. The simulation of circuit and result analysis of the circuit is carried out by using Matlab/simulink software. The comparison between existing topology and proposed topology is given. The results are discussed and presented.